Legal Analysis Of The Recitation Of Manaqib Wali Allah In Banjar Society, Indonesia - Muhammad Firjatullah; Rahmat Fadillah; Mohd Hatta Md Hani; Nurdin, Nurdin (Sharia Journal and Education Center Publishing, 2024)
Abstract This research examines in more depth the view of Islamic law towards traditions in society, for example the reading of manaqib. The tradition of reading manaqib was born or emerged as a result of the development of Islam in Mandomai Village which was spread by traders from Kuin, South Kalimantan. This tradition is a legacy of previous Banjar muftis. When reading manaqib, Banjar people usually always prepare various kinds of cake, bitter coffee, sweet coffee, milk and other foods. The tradition of reading manaqib that was born in society is a tradition that contains Islamic values. For the community, reading manaqib is a good example of a medium for keeping in touch and a good tradition that must be continued. The community's motivation for reading manaqib varies, including tabarukkan, increasing one's sustenance, and a sign of gratitude to Allah SWT. This research uses a qualitative approach, literature study and also interviews with several informants. The Islamic legal view of this tradition is permissible as long as there is no shirk or ascribing partners to Allah in it. Keywords: Manaqib, Islamic Law, Indonesia Penelitian ini mengkaji lebih dalam mengenai pandangan hukum islam terhadap tradisi di masyarakat contohnya pembacaan manaqib ini. Tradisi pembacaan manaqib lahir atau muncul akibat dari pengembangan Islam di Kelurahan Mandomai yang disebarkan oleh pedagang-pedagang dari Kuin, Kalimantan Selatan. Tradisi ini merupakan warisan mufti Banjar terdahulu. Di waktu pembacaan manaqib, biasanya di masyarakat Banjar selalu menyiapkan berbagai macam wadai, kopi pahit, kopi manis, susu dan makanan lainnya. Tradisi pembacaan manaqib yang lahir di masyarakat merupakan tradisi yang mengandung nilai nilai islam. Bagi masyarakat, pembacaan manaqib merupakan contoh yang baik media untuk bersilaturahmi dan tradisi baik yang harus terus dilanjutkan. Motivasi dari masyarakat dalam pembacaan manaqib bermacam-macam diantaranya tabarukkan, menambah rezeki, dan tanda syukur kepada Allah Swt. Penelitian ini menggunakan pendekatan kualitatif, studi pustaka dan juga wawancara kepada beberapa informan. Pandangan hukum islam terhadap tradisi ini boleh dilakukan asal tidak ada syirik atau menyekutukan Allah didalamnya. Kata Kunci: Manaqib, Hukum Islam, Indonesia